Anti–SARS-CoV-2 Natural Products as Potentially Therapeutic Agents - Kim, Cheorl-Ho (Frontiers in Pharmacology, 2021)
Severe acute respiratory syndrome–related coronavirus-2 (SARS-CoV-2), a β-coronavirus, is the cause of the recently emerged pandemic and worldwide outbreak of respiratory disease. Researchers exchange information on COVID-19 to enable collaborative searches. Although there is as yet no effective antiviral agent, like tamiflu against influenza, to block SARS-CoV-2 infection to its host cells, various candidates to mitigate or treat the disease are currently being investigated. Several drugs are being screened for the ability to block virus entry on cell surfaces and/or block intracellular replication in host cells. Vaccine development is being pursued, invoking a better elucidation of the life cycle of the virus. SARS-CoV-2 recognizes O-acetylated neuraminic acids and also several membrane proteins, such as ACE2, as the result of evolutionary switches of O-Ac SA recognition specificities. To provide information related to the current development of possible anti–SARS-COV-2 viral agents, the current review deals with the known inhibitory compounds with low molecular weight. The molecules are mainly derived from natural products of plant sources by screening or chemical synthesis via molecular simulations. Artificial intelligence–based computational simulation for drug designation and large-scale inhibitor screening have recently been performed. Structure–activity relationship of the anti–SARS-CoV-2 natural compounds is discussed.